FACING THE CHALLENGES OF ELEMENTARY EDUCATION: FROM DIGITAL DIVIDE TO TEACHER DEVELOPMENT - Elliyani, Eli; Edwita; Nurhasanah, Nina (Universitas Negeri Surabaya, 2025)
Phenomenon/Issue: The phenomenon explored in this study is the digital divide and its impact on elementary education, specifically how disparities in access to technology and digital literacy training affect student learning outcomes. In many developing regions, such as rural areas in Indonesia, schools face a significant lack of digital infrastructure, which prevents students from benefiting from technology-enhanced learning. Furthermore, even in urban areas where digital tools are available, gaps in teacher development hinder the effective integration of technology into classroom instruction. Purpose: The purpose of this study is to examine how the digital divide and teacher development challenges intersect to affect educational outcomes in elementary schools. Novelty: This research is novel in its focus on the interplay between the digital divide and teacher development, an area that is often addressed separately in education research. Research Methods: This study adopts a qualitative research approach, utilizing semi-structured interviews with teachers and administrators, as well as classroom observations to gather in-depth insights. Thematic analysis is used to identify key patterns and challenges related to digital access and teacher development. Results: The results indicate that while access to technology is a major barrier in rural schools, even in urban settings, inadequate teacher training hampers the effective use of digital tools. Teacher development, especially in digital literacy, emerges as a critical factor in bridging the digital divide